Foundations under pressure: Qualitative interviews on the impact of prolonged pandemic and public health measures on Ontario youth and young adults - Laurel C. Austin; Makayla Nunes Gomes; Sebastián Chávez; Celina Degano (PLoS ONE, 2025)
Introduction Foundations of youth and young adults’ (YYAs) lives were shaken by the prolonged COVID-19 pandemic. This study explores how over a year of pandemic, with several periods of stay-at-home orders, impacted Ontario YYAs and important foundations that influence their development and future wellbeing. Methods Semi-structured interviews were conducted April – June 2021 during stay-at-home orders. Nineteen Ontario YYAs, age 16–21, were asked how relationships, education, work, and important events had been impacted by the pandemic and public health responses, and how they had coped. Reflexive thematic analysis was used to iteratively engage with data to distill themes. Respondents included: eight high school students, ten post-secondary students, one full time employed. Results Three main themes were identified. First, disruptions to individual agency and life course (theme), included (subthemes): drastic shift to increased time and isolation at home; feeling responsible for others’ health and safety; learning and professional development suffered; precarious employment; and lost beginnings and endings to important transitions. Second, relationships and connectedness changed (theme), included (subthemes): Friendships were altered; family dynamics changed; and international students faced unique challenges. Third, wellbeing and coping (theme), included (sub-themes): stress was high; coping methods were diverse; and connecting digitally was suboptimal. Some friendships were lost; some grew closer. Those in their last year of high school/university in spring 2020 or 2021 lost important transitional endings (graduation, etc.). Those starting post-secondary in fall 2020 also lost transitional beginnings (e.g., leaving home, on-campus experience, meeting new friends). Conclusions There is need for further research to assess long-term impacts, especially among YYAs who had family members at severe risk and those who graduated high school during the pandemic. Public health practitioners should work with high schools and post-secondary schools to develop approaches to limit the severity of altered schooling and important transitions in future upheavals.